Perbedaan Pengaruh Media Tanam Serbuk Gergaji dan Jerami Padi Terhadap Pertumbuhan Jamur Tiram Putih (Pleurotus ostreatus) - Baiq Farhatul Wahidah; Firman Adi Saputra (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2015)
This research is an experimental research that aims to identify differences effect of growing media sawdust and rice straw on mycelium development time, the number of fruiting bodies and wet weight of Pleurotus ostreatus grown in the media (baglog). This research conducted in the Botanical Laboratory, Biology department, UIN Alauddin Makassar. The method in this research is completely randomized design with two types of growing media treatment. Each treatment consists of five repetitions obtained 10 baglog in observation. The data obtained were analyzed using inferential statistics t test, confidence level 0.05 through software SPSS 16.0. The results showed that there was a significant differences between the growth of Pleurotus ostreatus grown on rice straw media and sawdust media.Keywords: Pleurotus ostreatus, sawdust and rice straw media, the mycelium growth, the number of fruiting bodies